Level of knowledge about contraceptive methods in nursing university student - Arreguin Jiménez, Manuel Antonio (2022)
Objective: To determine the level of knowledge about contraceptive methods in undergraduate nursing students. Method: Quantitative cross-sectional study. The study was carried out in the period from June to August 2022. Students enrolled in the nursing degree at a private university in the Laja-Bajío region of Guanajuato, Mexico participated. The level of knowledge questionnaire on contraceptive methods was used. Main Results: 125 students between 18-27 years old participated, where females predominated (68%). The level of knowledge about contraceptive methods predominates the average level with 64%. General conclusion: Students enrolled in a health program have average knowledge about contraceptive methods, so this is advisable to delve into issues about their effectiveness and prevention of Sexually Transmitted Diseases in the study plans.